Composite solid electrolyte material for large cylindrical battery and preparation method thereof

CN122576348BActive Publication Date: 2026-10-30ANHUI VOLT TIMES NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610916554.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-30
Estimated Expiration
2046-06-24

AI Technical Summary

Technical Problem

然而,传统液态电解液体系在高能量密度圆柱电池中存在显著的安全隐患:液态电解液易挥发、漏液及热失控风险大,同时在卷绕结构中难以保持均匀分布,导致极片间局部应力与界面老化问题,为提升能量密度与安全性,业界逐渐将目光转向固态电解质体系

Benefits of technology

[0026]本发明利用3-氯丙基三甲氧基硅烷与N-甲基咪唑发生季铵化反应制备咪唑基硅烷偶联剂,同时本发明利用3-(2,3-环氧丙氧)丙基三甲氧基硅烷与聚醚胺发生开环反应后加入烯丙胺基五氯环三磷腈和聚乙二醇二缩水甘油醚制备改性硅烷偶联剂,其中聚醚胺的部分氨基基团可以与烯丙胺基五氯环三磷腈中的氯原子发生取代反应,且加入聚乙二醇二缩水甘油醚作为缚酸剂,其中烯丙胺基五氯环三磷腈为利用烯丙胺与六氯环三磷腈发生取代反应制成,六氯环三磷腈作为一类具有代表性的主链由磷、氮元素交替排列的有机-无机杂化材料,其具有较强的热稳定性和突出的结构柔性,以烯丙胺基五氯环三磷腈作为交联点与聚醚胺柔性长链连接成为网络结构,然后将咪唑基硅烷偶联剂和改性硅烷偶联剂在锂镧锆氧化物活性陶瓷表面接枝,锂镧锆氧化物活性陶瓷表面富集的聚醚链段,构建了更多的Li+传输通道,同时赋予电解质出色的阻燃特性,有利于固态电解质在锂金属电池应用中安全性的提升,同时锂镧锆氧化物活性陶瓷表面引入带正电荷的咪唑基团能够通过静电作用锚定溶剂分子和阴离子,促进了锂离子的传输效率。本发明将功能化锂镧锆氧化物活性陶瓷纳米颗粒引入至有机聚合物静电纺丝骨架中,构建出连续导锂的柔性无机-聚合物纤维网络,并在其孔隙中注入含锂聚乙二醇二丙烯酸酯单体进行原位聚合,且功能化锂镧锆氧化物活性陶瓷中引入烯丙胺基五氯环三磷腈的双键结构可以和聚乙二醇二丙烯酸酯进行共聚,形成互穿型固态结构,不仅实现了无机增强相与聚合物基体的化学键合与结构兼容,同时兼顾了力学柔性与离子电导性,适用于大圆柱电池的自动化卷绕生产工艺,同时保证了电池的长循环寿命和高安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122576348B_ABST
    Figure CN122576348B_ABST
Patent Text Reader

Abstract

The application relates to the field of solid electrolytes, and discloses a composite solid electrolyte material for large cylindrical batteries and a preparation method thereof, the composite solid electrolyte material comprising: an organic polymer, a functionalized lithium lanthanum zirconium oxide active ceramic, polyethylene glycol diacrylate, a conductive lithium salt, a thermal initiator and an organic solvent; the functionalized lithium lanthanum zirconium oxide active ceramic is prepared by grafting an imidazole-based silane coupling agent and a modified silane coupling agent on the surface of lithium lanthanum zirconium oxide active ceramic, wherein the imidazole-based silane coupling agent is prepared by reacting 3-chloropropyltrimethoxysilane with N-methyl imidazole; and the modified silane coupling agent is prepared by crosslinking allylamine pentachlorocyclotriphosphazene and polyethylene glycol diglycidyl ether after ring opening of 3-(2,3-epoxypropoxy) propyltrimethoxysilane and polyether amine, the application realizes chemical bonding and structural compatibility of the inorganic reinforcing phase and the polymer matrix, simultaneously considers mechanical flexibility and ionic conductivity, and guarantees long cycle life and high safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid-state electrolyte technology, specifically relating to a composite solid-state electrolyte material for large cylindrical batteries and its preparation method. Background Technology

[0002] With the rapid development of new energy vehicles and high-end energy storage systems, cylindrical lithium batteries are gradually becoming an important direction in the high-end energy storage field due to their high energy density, excellent heat dissipation characteristics, and highly automated production processes. However, traditional liquid electrolyte systems pose significant safety hazards in high-energy-density cylindrical batteries: liquid electrolytes are prone to volatility, leakage, and thermal runaway, and are difficult to maintain uniform distribution in the winding structure, leading to localized stress and interface aging problems between electrodes. To improve energy density and safety, the industry is gradually turning its attention to solid-state electrolyte systems.

[0003] However, existing solid-state electrolyte materials still face some technical challenges when applied to large cylindrical structures: While oxide-based electrolytes (such as LLZO and LATP) possess high ionic conductivity and a wide electrochemical window, their high rigidity makes them difficult to bond tightly to electrodes, failing to meet the flexibility and interfacial extensibility requirements of wound structures. Single polymer-based electrolytes (such as PEO and PAN), while soft and easy to process, exhibit low room-temperature ionic conductivity and insufficient thermal stability, making them prone to interfacial decomposition and electrochemical failure in high-voltage systems. Furthermore, inorganic-organic composite systems generally suffer from interfacial discontinuities, particle agglomeration, and mechanical stress concentration, resulting in low ionic conductivity of the composite electrolyte membrane and poor compatibility with high-voltage electrodes / lithium metal electrodes, leading to cycle degradation and decreased safety. Summary of the Invention

[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide a composite solid electrolyte material for large cylindrical batteries and its preparation method. Functionalized lithium lanthanum zirconium oxide active ceramics are introduced into an organic polymer electrospinning framework to construct a continuously lithium-conducting flexible inorganic-polymer fiber network. Lithium-containing polyethylene glycol diacrylate monomers are injected into the pores for in-situ polymerization, forming an interpenetrating solid structure. This not only achieves chemical bonding and structural compatibility between the inorganic reinforcing phase and the polymer matrix, but also balances mechanical flexibility and ionic conductivity. It is suitable for automated winding production processes of large cylindrical batteries, while ensuring long cycle life and high safety of the battery.

[0005] The objective of this invention can be achieved through the following technical solutions:

[0006] A composite solid electrolyte material for large cylindrical batteries comprises the following components by weight: 30-50 parts of organic polymer, 10-20 parts of functionalized lithium lanthanum zirconium oxide active ceramic, 0.5-1 part of polyethylene glycol diacrylate, 5-10 parts of conductive lithium salt, 0.02-0.06 parts of thermal initiator, and 10-25 parts of organic solvent.

[0007] The functionalized lithium lanthanum zirconium oxide active ceramic is prepared by grafting imidazole-based silane coupling agents and modified silane coupling agents onto the surface of lithium lanthanum zirconium oxide active ceramics; the imidazole-based silane coupling agent is prepared by quaternization reaction of 3-chloropropyltrimethoxysilane with N-methylimidazolium; the modified silane coupling agent is prepared by ring-opening reaction of 3-(2,3-epoxypropoxy)propyltrimethoxysilane with polyetheramine followed by crosslinking with allylaminopentachlorocyclotriphosphazene and polyethylene glycol diglycidyl ether; the allylaminopentachlorocyclotriphosphazene is prepared by substitution reaction of allylamine with hexachlorocyclotriphosphazene.

[0008] Preferably, the organic polymer is one or more of polyacrylonitrile, polyvinylidene fluoride, and polyvinylidene fluoride-co-hexafluoropropylene.

[0009] Preferably, the lithium lanthanum zirconium oxide active ceramic is one of lithium lanthanum zirconium tantalum oxide, aluminum-doped lithium lanthanum zirconium oxide, and niobium-doped lithium lanthanum zirconium oxide; the conductive lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.

[0010] Preferably, the thermal initiator is azobisisobutyronitrile or benzoyl peroxide; and the organic solvent is N,N-dimethylformamide.

[0011] Preferably, the preparation method of the functionalized lithium lanthanum zirconium oxide active ceramic includes the following steps:

[0012] A. Mix 3-chloropropyltrimethoxysilane, N-methylimidazolium and N,N-dimethylformamide evenly and stir at 75~85℃ for 45~48h. Then dissolve in deionized water, extract with dichloromethane and evaporate under vacuum to prepare imidazolium silane coupling agent.

[0013] B. Dissolve hexachlorocyclotriphosphazene in tetrahydrofuran, and slowly add a mixed solution of allylamine, tetrahydrofuran and triethylamine dropwise over 20 min with stirring. Place the mixture in an ice-water bath and react for 3-5 h. After the reaction is complete, filter, wash and dry to prepare allylamine pentachlorocyclotriphosphazene.

[0014] C. Mix 3-(2,3-epoxypropoxy)propyltrimethoxysilane and methanol evenly, then add it dropwise to a mixed solution of polyetheramine and methanol under vigorous stirring. Stir at 45-55℃ for 20-24 hours. Then add allylaminopentachlorocyclotriphosphazene and polyethylene glycol diglycidyl ether. Stir at room temperature for 2-4 hours. Remove the solvent by rotary evaporation to prepare the modified silane coupling agent.

[0015] D. Disperse lithium lanthanum zirconium oxide active ceramics in deionized water, then add imidazole silane coupling agent and modified silane coupling agent, and stir continuously at 70~85℃ for 20~24h. After the reaction is completed, centrifuge, wash and dry to prepare functionalized lithium lanthanum zirconium oxide active ceramics.

[0016] Preferably, in step C, the mass ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, polyetheramine, allylaminopentachlorocyclotriphosphazene, and polyethylene glycol diglycidyl ether is 0.1~0.2:0.8~1.7:0.1:0.2.

[0017] Preferably, in step D, the mass ratio of lithium lanthanum zirconium oxide active ceramic, imidazole silane coupling agent and modified silane coupling agent is 1:0.04~0.08:0.04~0.08.

[0018] The preparation method of the composite solid electrolyte material for large cylindrical batteries as described above includes the following steps:

[0019] S1. Weigh each component according to the weight parts, dissolve the organic polymer in the organic solvent, add the functionalized lithium lanthanum zirconium oxide active ceramic, stir at room temperature for 12~24h to obtain the electrospinning solution.

[0020] S2. Electrospun nanofiber membranes are obtained by electrospunting solution using electrospunting technology and hot-pressing composite and thinning treatment.

[0021] S3. Heat polyethylene glycol diacrylate to 55°C to a fluid state, then add conductive lithium salt and mix evenly. Subsequently, add thermal initiator to form a homogeneous precursor solution.

[0022] S4. The precursor solution is cast onto an electrospun nanofiber membrane and heated in an inert atmosphere to carry out an in-situ polymerization reaction, thereby preparing a composite solid electrolyte material for large cylindrical batteries.

[0023] Preferably, the electrospinning technology in step S2 is as follows: the electrospinning solution is transferred to a syringe containing a stainless steel needle. During the electrospinning process, a high voltage of 14kV, a negative pressure of -2kV, and a receiving distance of 22cm are used. The spraying speed is 1mL / h, and the spinning time is 4h. Then, the electrospinned fibers are collected on an automatically wound smooth kraft paper. The hot-pressing composite temperature is 100℃, and the thickness of the electrospinned nanofiber membrane after thinning treatment is 15~20μm.

[0024] Preferably, in step S4, the inert atmosphere is argon or nitrogen, the heating temperature is 40~90℃, and the heating time is 0.5~5h.

[0025] The beneficial effects of this invention are:

[0026] This invention utilizes the quaternization reaction of 3-chloropropyltrimethoxysilane with N-methylimidazolium to prepare imidazole-based silane coupling agents. Simultaneously, this invention utilizes the ring-opening reaction of 3-(2,3-epoxypropoxy)propyltrimethoxysilane with polyetheramine, followed by the addition of allylaminopentachlorocyclotriphosphazene and polyethylene glycol diglycidyl ether to prepare modified silane coupling agents. In this process, some amino groups of the polyetheramine can undergo substitution reactions with the chlorine atoms in allylaminopentachlorocyclotriphosphazene, and polyethylene glycol diglycidyl ether is added as an acid-binding agent. Phosphazene was prepared by a substitution reaction between allylamine and hexachlorocyclotriphosphazene. Hexachlorocyclotriphosphazene, as a representative organic-inorganic hybrid material with alternating phosphorus and nitrogen elements in its main chain, exhibits strong thermal stability and outstanding structural flexibility. Allylamine-based pentachlorocyclotriphosphazene was used as a crosslinking point to connect with flexible long chains of polyetheramine to form a network structure. Then, imidazole-based silane coupling agents and modified silane coupling agents were grafted onto the surface of lithium lanthanum zirconium oxide active ceramics. The polyether segments enriched on the surface of the lithium lanthanum zirconium oxide active ceramics constructed a larger Li... + The lithium ion transport channel, while imparting excellent flame-retardant properties to the electrolyte, is beneficial to improving the safety of solid electrolytes in lithium metal battery applications. Simultaneously, the introduction of positively charged imidazole groups on the surface of the lithium lanthanum zirconium oxide active ceramic enables electrostatic anchoring of solvent molecules and anions, promoting lithium-ion transport efficiency. This invention introduces functionalized lithium lanthanum zirconium oxide active ceramic nanoparticles into an organic polymer electrospinning framework, constructing a continuously lithium-conducting flexible inorganic-polymer fiber network. Lithium-containing polyethylene glycol diacrylate monomers are injected into the pores for in-situ polymerization. Furthermore, the double bond structure of allylaminopentachlorocyclotriphosphazene introduced into the functionalized lithium lanthanum zirconium oxide active ceramic can copolymerize with polyethylene glycol diacrylate to form an interpenetrating solid structure. This not only achieves chemical bonding and structural compatibility between the inorganic reinforcing phase and the polymer matrix but also balances mechanical flexibility and ionic conductivity, making it suitable for automated winding production processes of large cylindrical batteries while ensuring long cycle life and high safety. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 This is a scanning electron microscope image of the electrospun nanofiber membrane prepared in Example 2 of the present invention;

[0029] Figure 2 This is the XRD pattern of the composite solid electrolyte material prepared in Example 2 of this invention. Detailed Implementation

[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0031] Example 1: A method for preparing a functionalized lithium lanthanum zirconium oxide active ceramic includes the following steps:

[0032] A. Take 2.25 mL of 3-chloropropyltrimethoxysilane, 1 mL of N-methylimidazolium and 15 mL of N,N-dimethylformamide, mix them evenly and stir at 80 °C for 48 h, then dissolve them in deionized water, extract with dichloromethane and evaporate under vacuum to prepare imidazolium silane coupling agent.

[0033] B. Dissolve 6.95g of hexachlorocyclotriphosphazene in 50mL of tetrahydrofuran. Under stirring, slowly add a mixed solution containing 1.42g of allylamine, 10mL of tetrahydrofuran and 2.05g of triethylamine over 20min. The mixture is placed in an ice-water bath and reacted for 4h. After the reaction is completed, the mixture is filtered, washed and dried to prepare allylamine pentachlorocyclotriphosphazene.

[0034] C. Take 0.15g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 20mL of methanol and mix them evenly. Then, add the mixture dropwise to a mixed solution of 1.5g of polyetheramine D2000 and 50mL of methanol under vigorous stirring. Stir at 50℃ for 24h. Then, add 0.1g of allylaminopentachlorocyclotriphosphazene and 0.2g of polyethylene glycol diglycidyl ether. Stir at room temperature for 3h. Remove the solvent by rotary evaporation to prepare the modified silane coupling agent.

[0035] D. Take 1g of lithium lanthanum zirconium tantalum oxide (Li 6.5La3Zr 1.5 Ta 0.5 O 12 ,LLZO) was dispersed in 100 mL of deionized water, and then 0.05 g of imidazole silane coupling agent and 0.06 g of modified silane coupling agent were added. The mixture was stirred continuously at 80 °C for 24 h. After the reaction was completed, the mixture was centrifuged, washed and dried to prepare functionalized lithium lanthanum zirconium oxide active ceramics.

[0036] Example 2 A composite solid electrolyte material for large cylindrical batteries, comprising the following components by weight: 33 parts polyacrylonitrile, 12 parts functionalized lithium lanthanum zirconium oxide active ceramic prepared in Example 1, 0.6 parts polyethylene glycol diacrylate, 5.5 parts lithium bis(trifluoromethanesulfonyl)imide, 0.02 parts azobisisobutyronitrile, and 12 parts N,N-dimethylformamide.

[0037] The above-mentioned method for preparing composite solid electrolyte materials for large cylindrical batteries includes the following steps:

[0038] S1. Weigh each component according to the weight parts, dissolve polyacrylonitrile in N,N-dimethylformamide, add functionalized lithium lanthanum zirconium oxide active ceramic, stir at room temperature for 16 hours to obtain electrospinning solution.

[0039] S2. The electrospinning solution was transferred to a syringe equipped with a stainless steel needle. During the electrospinning process, a high voltage of 14 kV, a negative voltage of -2 kV, and a receiving distance of 22 cm were used. The injection rate was 1 mL / h, and the spinning time was 4 h. The electrospinned fibers were then collected on an automatically wound smooth kraft paper and subjected to a hot-pressing process at 100℃ to obtain an electrospinned nanofiber membrane with a thickness of 15 μm. The scanning electron microscope image is shown below. Figure 1 As shown;

[0040] S3. Heat polyethylene glycol diacrylate to 55°C to a fluid state, then add lithium bis(trifluoromethanesulfonyl)imide and mix evenly. Subsequently, add azobisisobutyronitrile to form a homogeneous precursor solution.

[0041] S4. The precursor solution was cast onto an electrospun nanofiber membrane. After the membrane was completely impregnated, it was stored at 70°C for 2 hours to ensure complete polymerization. The operation was carried out in an argon-filled glove box (Mikrouna, H2O, O2 ≤ 0.1ppm) to prepare a composite solid electrolyte material for large cylindrical batteries. The XRD pattern of the composite solid electrolyte material is shown below. Figure 2 As shown.

[0042] Example 3 A composite solid electrolyte material for large cylindrical batteries, comprising the following components by weight: 41 parts polyacrylonitrile, 15 parts functionalized lithium lanthanum zirconium oxide active ceramic prepared in Example 1, 0.8 parts polyethylene glycol diacrylate, 7.2 parts lithium bis(trifluoromethanesulfonyl)imide, 0.03 parts azobisisobutyronitrile, and 20 parts N,N-dimethylformamide.

[0043] The above-mentioned method for preparing composite solid electrolyte materials for large cylindrical batteries includes the following steps:

[0044] S1. Weigh each component according to the weight parts, dissolve polyacrylonitrile in N,N-dimethylformamide, add functionalized lithium lanthanum zirconium oxide active ceramic, stir at room temperature for 16 hours to obtain electrospinning solution.

[0045] S2. The electrospinning solution is transferred to a syringe containing a stainless steel needle. During the electrospinning process, a high voltage of 14kV, a negative pressure of -2kV and a receiving distance of 22cm are used. The spraying speed is 1mL / h and the spinning time is 4h. Then, the electrospinned fibers are collected on an automatically wound smooth kraft paper and obtained an electrospinned nanofiber membrane with a thickness of 18μm through a 100℃ hot pressing process.

[0046] S3. Heat polyethylene glycol diacrylate to 55°C to a fluid state, then add lithium bis(trifluoromethanesulfonyl)imide and mix evenly. Subsequently, add azobisisobutyronitrile to form a homogeneous precursor solution.

[0047] S4. The precursor solution is cast onto an electrospun nanofiber membrane. After the membrane is fully impregnated, it is stored at 70°C for 2 hours to ensure complete polymerization. The operation is carried out in a glove box filled with argon (Mikrouna, H2O, O2≤0.1ppm) to prepare a composite solid electrolyte material for large cylindrical batteries.

[0048] Example 4 A composite solid electrolyte material for large cylindrical batteries, comprising the following components by weight: 48 parts polyacrylonitrile, 18 parts functionalized lithium lanthanum zirconium oxide active ceramic prepared in Example 1, 0.9 parts polyethylene glycol diacrylate, 9.3 parts lithium bis(trifluoromethanesulfonyl)imide, 0.05 parts azobisisobutyronitrile, and 23 parts N,N-dimethylformamide.

[0049] The above-mentioned method for preparing composite solid electrolyte materials for large cylindrical batteries includes the following steps:

[0050] S1. Weigh each component according to the weight parts, dissolve polyacrylonitrile in N,N-dimethylformamide, add functionalized lithium lanthanum zirconium oxide active ceramic, stir at room temperature for 16 hours to obtain electrospinning solution.

[0051] S2. The electrospinning solution is transferred to a syringe containing a stainless steel needle. During the electrospinning process, a high voltage of 14kV, a negative pressure of -2kV and a receiving distance of 22cm are used. The spraying speed is 1mL / h and the spinning time is 4h. Then the electrospinned fibers are collected on an automatically wound smooth kraft paper and a 20μm thick electrospinned nanofiber membrane is obtained by hot pressing at 100℃.

[0052] S3. Heat polyethylene glycol diacrylate to 55°C to a fluid state, then add lithium bis(trifluoromethanesulfonyl)imide and mix evenly. Subsequently, add azobisisobutyronitrile to form a homogeneous precursor solution.

[0053] S4. The precursor solution is cast onto an electrospun nanofiber membrane. After the membrane is fully impregnated, it is stored at 70°C for 2 hours to ensure complete polymerization. The operation is carried out in a glove box filled with argon (Mikrouna, H2O, O2≤0.1ppm) to prepare a composite solid electrolyte material for large cylindrical batteries.

[0054] Comparative Example 1: A method for preparing a functionalized lithium lanthanum zirconium oxide active ceramic includes the following steps:

[0055] A. Dissolve 6.95g of hexachlorocyclotriphosphazene in 50mL of tetrahydrofuran. Under stirring, slowly add a mixed solution containing 1.42g of allylamine, 10mL of tetrahydrofuran and 2.05g of triethylamine over 20min. The mixture is placed in an ice-water bath and reacted for 4h. After the reaction is completed, the mixture is filtered, washed and dried to prepare allylamine pentachlorocyclotriphosphazene.

[0056] B. Mix 0.15g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 20mL of methanol until homogeneous. Then, add the mixture dropwise to a solution of 1.5g of polyetheramine D2000 and 50mL of methanol under vigorous stirring. Stir at 50℃ for 24h. Then, add 0.1g of allylaminopentachlorocyclotriphosphazene and 0.2g of polyethylene glycol diglycidyl ether. Stir at room temperature for 3h. Remove the solvent by rotary evaporation to prepare the modified silane coupling agent.

[0057] C. Take 1g of lithium lanthanum zirconium tantalum oxide (Li 6.5 La3Zr 1.5 Ta 0.5 O 12 ,LLZO) was dispersed in 100mL of deionized water, and then 0.06g of modified silane coupling agent was added. The mixture was stirred continuously at 80℃ for 24h. After the reaction was completed, the mixture was centrifuged, washed and dried to prepare functionalized lithium lanthanum zirconium oxide active ceramics.

[0058] Comparative Example 2: A method for preparing a functionalized lithium lanthanum zirconium oxide active ceramic includes the following steps:

[0059] A. Take 2.25 mL of 3-chloropropyltrimethoxysilane, 1 mL of N-methylimidazolium and 15 mL of N,N-dimethylformamide, mix them evenly and stir at 80 °C for 48 h, then dissolve them in deionized water, extract with dichloromethane and evaporate under vacuum to prepare imidazolium silane coupling agent.

[0060] B. Take 0.15g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 20mL of methanol and mix them evenly. Then, add the mixture dropwise to a mixed solution of 1.5g of polyetheramine D2000 and 50mL of methanol under vigorous stirring. Stir at 50℃ for 24h and remove the solvent by rotary evaporation to prepare the modified silane coupling agent.

[0061] C. Take 1g of lithium lanthanum zirconium tantalum oxide (Li 6.5 La3Zr 1.5 Ta 0.5 O 12 ,LLZO) was dispersed in 100 mL of deionized water, and then 0.05 g of imidazole silane coupling agent and 0.06 g of modified silane coupling agent were added. The mixture was stirred continuously at 80 °C for 24 h. After the reaction was completed, the mixture was centrifuged, washed and dried to prepare functionalized lithium lanthanum zirconium oxide active ceramics.

[0062] Comparative Example 3: A method for preparing a functionalized lithium lanthanum zirconium oxide active ceramic includes the following steps:

[0063] A. Take 2.25 mL of 3-chloropropyltrimethoxysilane, 1 mL of N-methylimidazolium and 15 mL of N,N-dimethylformamide, mix them evenly and stir at 80 °C for 48 h, then dissolve them in deionized water, extract with dichloromethane and evaporate under vacuum to prepare imidazolium silane coupling agent.

[0064] B. Take 1g of lithium lanthanum zirconium tantalum oxide (Li 6.5 La3Zr 1.5 Ta 0.5 O 12 ,LLZO) was dispersed in 100 mL of deionized water, and then 0.05 g imidazolylsilane coupling agent and 0.06 g 3-(2,3-epoxypropoxy)propyltrimethoxysilane were added. The mixture was stirred continuously at 80 °C for 24 h. After the reaction was completed, the mixture was centrifuged, washed and dried to prepare functionalized lithium lanthanum zirconium oxide active ceramics.

[0065] Comparative Example 4: A composite solid electrolyte material for large cylindrical batteries, comprising the following components by weight: 41 parts polyacrylonitrile, 15 parts functionalized lithium lanthanum zirconium oxide active ceramic prepared in Comparative Example 1, 0.8 parts polyethylene glycol diacrylate, 7.2 parts lithium bis(trifluoromethanesulfonyl)imide, 0.03 parts azobisisobutyronitrile, and 20 parts N,N-dimethylformamide.

[0066] The preparation method of the composite solid electrolyte material for large cylindrical batteries described above is the same as in Example 3.

[0067] Comparative Example 5: A composite solid electrolyte material for large cylindrical batteries, comprising the following components by weight: 41 parts polyacrylonitrile, 15 parts functionalized lithium lanthanum zirconium oxide active ceramic prepared in Comparative Example 2, 0.8 parts polyethylene glycol diacrylate, 7.2 parts lithium bis(trifluoromethanesulfonyl)imide, 0.03 parts azobisisobutyronitrile, and 20 parts N,N-dimethylformamide.

[0068] The preparation method of the composite solid electrolyte material for large cylindrical batteries described above is the same as in Example 3.

[0069] Comparative Example 6: A composite solid electrolyte material for large cylindrical batteries, comprising the following components by weight: 41 parts polyacrylonitrile, 15 parts functionalized lithium lanthanum zirconium oxide active ceramic prepared in Comparative Example 3, 0.8 parts polyethylene glycol diacrylate, 7.2 parts lithium bis(trifluoromethanesulfonyl)imide, 0.03 parts azobisisobutyronitrile, and 20 parts N,N-dimethylformamide.

[0070] The preparation method of the composite solid electrolyte material for large cylindrical batteries described above is the same as in Example 3.

[0071] Performance testing

[0072] The performance of the composite solid electrolyte materials prepared in Examples 2-4 and Comparative Examples 4-6 was tested:

[0073] (1) Tensile property test: The tensile properties of the sample were tested using a universal testing machine. The data results are shown in Table 1.

[0074] (2) Heat resistance test: Under nitrogen conditions, the weight change of the sample in the range of room temperature to 800℃ was tested at a heating rate of 10℃ / min. The heat resistance of the sample was evaluated by the initial thermal decomposition temperature. The data results are shown in Table 1.

[0075] (3) Flame retardant performance test: The data results are shown in Table 1, which are expressed by the limiting oxygen index.

[0076] (4) Ionic conductivity test: The SS / SS symmetrical cells made from the samples were placed in a constant temperature chamber. The body impedance of the double steel cell was tested using an electrochemical workstation. The electrolyte ionic conductivity σ was calculated according to the following formula: σ=L / (Rb×S), where L represents the thickness of the electrolyte, Rb represents the body resistance, and S represents the effective area of ​​the electrolyte. The data results are shown in Table 1.

[0077] (5) Cyclic performance test: Using the composite solid electrolyte materials prepared in Examples 2-4 and Comparative Examples 4-6, NCM811 as the positive electrode and lithium metal sheet (Li) as the negative electrode, NCM811 electrolyte-Li full cell was assembled. The cycle performance of the battery from 2.75V to 4.3V was tested at 60℃. The preparation of NCM811 positive electrode sheet: First, PVDF was dissolved in N-methylpyrrolidone to prepare a binder with a mass fraction of 5%. Then, NCM811 and conductive carbon black were first dry-ground evenly, and then the binder was added for wet grinding. NCM811, conductive carbon black and PVDF were dispersed in N-methylpyrrolidone solvent in a weight ratio of 8:1:1. Finally, the slurry was evenly coated on aluminum foil and dried in a vacuum oven at 80℃ for 24h. The data results are shown in Table 1.

[0078] Table 1 Sample performance test results

[0079] Project Group Tensile strength / MPa Initial thermal decomposition temperature / °C Limiting oxygen index / % <![CDATA[Conductivity / S·cm -1 > <![CDATA[Initial discharge specific capacity / mAh·g -1 > Capacity retention rate after 100 cycles at 0.1°C / % Example 2 0.66 320.2 28.4 <![CDATA[8.71×10 -4 ]]> 174.6 80.2 Example 3 0.74 319.9 28.2 <![CDATA[8.63×10 -4 ]]> 171.7 80.1 Example 4 0.83 322.3 28.5 <![CDATA[7.98×10 -4 ]]> 165.1 79.6 Comparative Example 4 0.72 320.6 28.4 <![CDATA[7.95×10 -4 ]]> 151.2 76.1 Comparative Example 5 0.57 299.6 22.5 <![CDATA[8.61×10 -4 ]]> 170.9 80.0 Comparative Example 6 0.51 299.5 22.3 <![CDATA[5.92×10 -4 ]]> 144.6 68.5

[0080] As can be seen from the data in Table 1, the materials prepared in Examples 2-4 of this invention have high tensile strength, good heat resistance and flame retardancy, and the batteries prepared have high conductivity and good cycle performance. In Comparative Example 4, the functionalized lithium lanthanum zirconium oxide active ceramic without imidazole-based silane coupling agent showed a decrease in initial discharge specific capacity and capacity retention after 100 cycles at 0.1C compared to Examples 2-4. This is because the interaction between the positively charged imidazole groups and anions restricts anion migration, thereby promoting lithium-ion transport efficiency. In Comparative Example 5, the functionalized lithium lanthanum zirconium oxide active ceramic without allylaminopentachlorocyclotriphosphazene and polyethylene glycol diglycidyl ether was not introduced. In Comparative Example 6, the functionalized lithium lanthanum zirconium oxide active ceramic without modified silane coupling agent showed a decrease in tensile strength, initial thermal decomposition temperature, and limiting oxygen index compared to Examples 2-4. Furthermore, the conductivity, initial discharge specific capacity, and capacity retention after 100 cycles at 0.1C in Comparative Example 6 were also lower than those in Examples 2-4. This indicates that the introduction of modified silane coupling agent is beneficial for improving the mechanical properties, heat resistance, and flame retardant properties of the electrolyte material, and the prepared battery exhibits high conductivity and good cycle performance.

[0081] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0082] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A composite solid-state electrolyte material for large cylindrical batteries, characterized in that, It comprises the following components by weight: 30-50 parts organic polymer, 10-20 parts functionalized lithium lanthanum zirconium oxide active ceramic, 0.5-1 part polyethylene glycol diacrylate, 5-10 parts conductive lithium salt, 0.02-0.06 parts thermal initiator, and 10-25 parts organic solvent; The functionalized lithium lanthanum zirconium oxide active ceramic is prepared by grafting imidazole-based silane coupling agents and modified silane coupling agents onto the surface of lithium lanthanum zirconium oxide active ceramics; the imidazole-based silane coupling agent is prepared by quaternization reaction of 3-chloropropyltrimethoxysilane with N-methylimidazolium; the modified silane coupling agent is prepared by ring-opening reaction of 3-(2,3-epoxypropoxy)propyltrimethoxysilane with polyetheramine followed by crosslinking with allylaminopentachlorocyclotriphosphazene and polyethylene glycol diglycidyl ether; the allylaminopentachlorocyclotriphosphazene is prepared by substitution reaction of allylamine with hexachlorocyclotriphosphazene. The preparation method of the functionalized lithium lanthanum zirconium oxide active ceramic includes the following steps: A. Mix 3-chloropropyltrimethoxysilane, N-methylimidazolium and N,N-dimethylformamide evenly and stir at 75~85℃ for 45~48h. Then dissolve in deionized water, extract with dichloromethane and evaporate under vacuum to prepare imidazolium silane coupling agent. B. Dissolve hexachlorocyclotriphosphazene in tetrahydrofuran, and slowly add a mixed solution of allylamine, tetrahydrofuran and triethylamine dropwise over 20 min with stirring. Place the mixture in an ice-water bath and react for 3-5 h. After the reaction is complete, filter, wash and dry to prepare allylamine pentachlorocyclotriphosphazene. C. Mix 3-(2,3-epoxypropoxy)propyltrimethoxysilane and methanol evenly, then add it dropwise to a mixed solution of polyetheramine and methanol under vigorous stirring. Stir at 45-55℃ for 20-24 hours. Then add allylaminopentachlorocyclotriphosphazene and polyethylene glycol diglycidyl ether. Stir at room temperature for 2-4 hours. Remove the solvent by rotary evaporation to prepare the modified silane coupling agent. D. Disperse lithium lanthanum zirconium oxide active ceramics in deionized water, then add imidazole silane coupling agent and modified silane coupling agent, and stir continuously at 70~85℃ for 20~24h. After the reaction is completed, centrifuge, wash and dry to prepare functionalized lithium lanthanum zirconium oxide active ceramics.

2. The composite solid electrolyte material for large cylindrical batteries according to claim 1, characterized in that, The organic polymer is one or more of polyacrylonitrile, polyvinylidene fluoride, and polyvinylidene fluoride-co-hexafluoropropylene.

3. The composite solid electrolyte material for large cylindrical batteries according to claim 1, characterized in that, The lithium lanthanum zirconium oxide active ceramic is one of lithium lanthanum zirconium tantalum oxide, aluminum-doped lithium lanthanum zirconium oxide, and niobium-doped lithium lanthanum zirconium oxide; the conductive lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.

4. The composite solid electrolyte material for large cylindrical batteries according to claim 1, characterized in that, The thermal initiator is azobisisobutyronitrile or benzoyl peroxide; the organic solvent is N,N-dimethylformamide.

5. The composite solid electrolyte material for large cylindrical batteries according to claim 1, characterized in that, In step C, the mass ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, polyetheramine, allylaminopentachlorocyclotriphosphazene, and polyethylene glycol diglycidyl ether is 0.1~0.2:0.8~1.7:0.1:0.

2.

6. The composite solid electrolyte material for large cylindrical batteries according to claim 1, characterized in that, In step D, the mass ratio of lithium lanthanum zirconium oxide active ceramic, imidazole silane coupling agent, and modified silane coupling agent is 1:0.04~0.08:0.04~0.

08.

7. A method for preparing a composite solid electrolyte material for large cylindrical batteries according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Weigh each component according to the weight parts, dissolve the organic polymer in the organic solvent, add the functionalized lithium lanthanum zirconium oxide active ceramic, stir at room temperature for 12~24h to obtain the electrospinning solution. S2. Electrospun nanofiber membranes are obtained by electrospunting solution using electrospunting technology and hot-pressing composite and thinning treatment. S3. Heat polyethylene glycol diacrylate to 55°C to a fluid state, then add conductive lithium salt and mix evenly. Subsequently, add thermal initiator to form a homogeneous precursor solution. S4. The precursor solution is cast onto an electrospun nanofiber membrane and heated in an inert atmosphere to carry out an in-situ polymerization reaction, thereby preparing a composite solid electrolyte material for large cylindrical batteries.

8. The method for preparing composite solid electrolyte material for large cylindrical batteries according to claim 7, characterized in that, The electrospinning technology in step S2 is as follows: the electrospinning solution is transferred to a syringe containing a stainless steel needle. During the electrospinning process, a high voltage of 14kV, a negative pressure of -2kV, and a receiving distance of 22cm are used. The spraying speed is 1mL / h, and the spinning time is 4h. Then, the electrospinned fibers are collected on an automatically wound smooth kraft paper. The hot-pressing composite temperature is 100℃, and the thickness of the electrospinned nanofiber membrane after thinning treatment is 15~20μm.

9. The method for preparing composite solid electrolyte material for large cylindrical batteries according to claim 7, characterized in that, In step S4, the inert atmosphere is argon or nitrogen, the heating temperature is 40~90℃, and the heating time is 0.5~5h.

Citation Information

Patent Citations

  • Preparation method of lithium lanthanum zirconium oxide nanometer fiber, preparation method of composite film and solid battery application

    CN107316965A

  • Electrochemical cells with mobile electrolyte

    WO2018136176A1